Germline Stem and Progenitor Cell Aging in C. elegans - Tolkin, Theadora; Hubbard, E. Jane Albert (Frontiers in Cell and Developmental Biology, 2021)
Like many animals and humans, reproduction in the nematode C. elegans declines with age. This decline is the cumulative result of age-related changes in several steps of germline function, many of which are highly accessible for experimental investigation in this short-lived model organism. Here we review recent work showing that a very early and major contributing step to reproductive decline is the depletion of the germline stem and progenitor cell pool. Since many cellular and molecular aspects of stem cell biology and aging are conserved across animals, understanding mechanisms of age-related decline of germline stem and progenitor cells in C. elegans has broad implications for aging stem cells, germline stem cells, and reproductive aging.